Revisão taxonômica da família Rajidae no Brasil (Chondrichthyes, Elasmobranchii, Rajiformes) - Gomes, Ulisses Leite (2002)
A taxonomic review of the rajid fishes occurring in Brazilian waters were held. The taxonomic arrangement as well as recent captures of deep water specimens included in this study, increased in 37% the number of Brazilian Rajidae. New taxons and also new records of occurrence were described. A revision of external characters, useful for specific identification, was held to facilitate the identification in both laboratory and field work. The family Rajidae in Brazil showed to be the most diversified of batoid fishes with two subfamilies, five tribes, eleven genera and twenty six species representing 42% of the Brazilian marine rays. The genera Breviraja, Cruriraja and Malacoraja are recorded for the first time in Brazilian water as does the species Breviraja spinosa, Cruriraja rugosa, Dipturus garricki, Dipturus teevani, Dipturus garricki and Rajella purpuriventralis. New species recognized in the present study are, Dipturus sp2, Dipturus sp3 e Malacoraja sp. The species who had their expanded occurrence records in Brazilian waters are Rajella sadowskii, Dipturus leptocauda, Sympterygia acuta and Gurgesiella dorsalifera. As seen in literature, the rajids have a close relationship with the sea botton. The main diet are crustaceans, polichetes, nematoids, cephalopods and teleost f ishes. Distribution data has revealed that the rajids from the slope presents a great distribution range. The mouth of the main rivers, acting directly abiotic factors, presented important influence in rajid distribution. The continental slope from Rio de Janeiro to the south of Brazil are mostly sandy, allowing a wide latitudinal range of the coastal rajids.With few specimens kept in scientific collections limit the taxonomic and biological knowledgement of certain taxons.